Organizational Differences in Rates of Learning: Evidence from the Adoption of Minimally Invasive Cardiac Surgery - Pisano, Gary P.; Bohmer, Richard M.J.; Edmondson, Amy C. (Management Science, 2001)
This paper examines learning curves in the health care setting to determine whether organizations achieve performance improvements from cumulative experience at different rates. Although extensive research has shown that cumulative experience leads to performance improvement across numerous contexts, the question of how much of this improvement is due to mere experience and how much is due to collective learning processes has received little attention. We argue that organizational learning processes may allow some organizations to benefit more than others from equivalent levels of experience. We thus propose that learning curves can vary across organizations engaged in the same “learning task,” due to organizational learning effects. To investigate this proposition, we investigate cardiac surgery departments implementing a new technology for minimally invasive cardiac surgery. Data on operative procedure times from a sample of 660 patients who underwent the new operation at 16 different institutions are analyzed. The results confirm that cumulative experience is a significant predictor of learning, and further reveal that the slope of the learning curve varies significantly across organizations. Theoretical and practical implications of the work are discussed.